PENGARUH EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (KASUS PADA PERUSAHAAN SEKTOR PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015) - Munggaran, Andri; Mukaram, Mukaram; Sarah, Ira Siti (Jurnal Riset Bisnis dan Investasi, 2017)
This research aims to determine the influence, direction, and significance of EPS on stock prices in the property, real estate, and building construction industry which is listed on the Indonesia Stock Exchange period of 2011 to 2015. Type of this study is a study where data used in this study is secondary data generated from company reports that have been available. Population in this research is all company of property, real estate, and building construction in IDX and usually report their company financial result in period 2011 until 2015. Total of existing population are 46 companies with 230 samples data which drawn by purposive sampling method. This is a sampling method that takes an object with certain criteria. The data analysis conducted with simple linear regression analysis and correlation analysis. The hypothesis analysis using t test and F test. The result of analysis shows that EPS have positive and significant effect to stock price, proved with correlation coefficient value 0,711 and probability value 0.000 less than 0,05.